PRDX2 induces tumor immune evasion by modulating the HDAC3-Galectin-9 axis in lung adenocarcinoma cells - Yunjia Dong; Anqi Cheng; Jiawei Zhou; Jianqiang Guo; Yafeng Liu; Xuan Li; Maoqian Chen; Dong Hu; Jing Wu (Journal of Translational Medicine)
Abstract Background PRDX2 is significantly expressed in various cancers and is associated with the proliferation of tumor cells. Nonetheless, the precise mechanism of PRDX2 in tumor immunity remains incompletely understood. This study aims to investigate the impact of PRDX2, which is highly expressed in lung adenocarcinoma, on T cells in the tumor immune microenvironment, and its immune action target to promote the immune escape of lung cancer cells, to provide a theoretical basis for lung adenocarcinoma treatment with PRDX2 as the target. Methods Mouse animal models to verify the effect of Conoidin A treatment on tumor growth and T cell infiltration. Flow cytometry and Western blot verified tumor cell apoptosis in the in vitro co-culture system as well as granzyme B and perforin expression in T cells. RNA-Seq was used to obtain the downstream immune molecule. si-RNA knockdown of Galectin-9 was co-cultured with T cells in vitro. Immunofluorescence and Western blot verified that PRDX2 regulates Galectin-9 expression through HDAC3. Results PRDX2 expression was negatively correlated with CD8+ T cell expression in LUAD patients. Inhibition of PRDX2 significantly enhanced T-cell killing of LUAD cells and reduced tumor load in both in vitro and in vivo models. Mechanistically, Conoidin A or shRNA_PRDX2 decreased Galectin-9 expression by down-regulating the phosphorylation of HDAC3, consequently enhancing the infiltration and function of CD8+ T cells. Conclusions This study reveals the role of the PRDX2/HDAC3/Galectin-9 axis in LUAD immune escape and indicates Galectin-9 as a promising target for immunotherapy.